نقض الاجتهاد - الزيداني، ضيف الله بن هادي بن علي (جامعة الملك خالد, 2015)
هذا البحث يدرس مسألة أصولية وهي متى ينقض الحكم الصادر من المجتهد أو القاضي، ويبين البحث أن الدليل الشرعي قطعي وظني، فالقطعي ينقض الحكم المخالف له اتفاقا، والمخالف للظني محل اختلاف وتفصيل، ونقض الحكم في حق مجتهد، هل يتعداه إلى مقلديه ؟، وفصل البحث فيما كان قبل العمل وبعده، وبين ما تعلق به حكم حاكم، وما ليس كذلك. مع الاستدلال والترجيح والتوثيق.
This research studies a fundamental issue. It's when to invalidate the judgment of the industrious or the judge .The research explains that legal evidences can be decisive or indecisive. If it violates a decisive rule it is invalidated by all means, and opinions are different if it violates an indecisive rule .And if a judgment of an industrious is invalidated, does that apply to those who imitate or follow his opinion? The research has also explained what is before or after the action, and if by virtue of governor or not, with reasoning, weighing and documentation.
Keywords: أصول الفقه -- الاجتهاد الفقهي -- نقض الاجتهاد